Local Wisdom-Based Cultural Arts Education to Foster Character Building in Fifth Grade Students at SD Inpres Bumi Sagu - ⁠Elfira Rusli; Kadek Hariana; ⁠Surahman Wilade; Rizal Rizal (Journal of Educational Sciences, 2026)
Along with the rapid development of globalization, the integration of regional cultural values in education has become increasingly important, particularly in strengthening the character of students from an early age. This study aims to describe the implementation of local wisdom-based cultural arts learning in building the character of fifth-grade students at SD Inpres Bumi Sagu. The research employed a descriptive qualitative method with data collected through interviews, document analysis, and observation. The subjects included the principal, homeroom teachers, dance teachers, and students as the primary participants. The findings reveal that local wisdom-based cultural arts learning at SD Inpres Bumi Sagu has been carried out effectively, although it remains an extracurricular activity and has not yet been fully integrated into the Merdeka Curriculum syllabus. The school successfully adopted the Torata Dance, a traditional welcoming dance from Central Sulawesi, as the main learning medium. The process was structured through initial orientation, dance practice, and closing activities that emphasized the philosophical and religious values of the local culture. Strong support from both the school and parents contributed to the success of the program. Students showed high enthusiasm, demonstrated the dance well, and understood its cultural meaning and origins. Moreover, this learning approach not only improved artistic skills but also fostered positive character traits such as hard work, creativity, responsibility, and religiosity.